2022
DOI: 10.1111/jne.13109
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of 177Lu‐DOTATATE peptide receptor radionuclide therapy and fluzoparib for treatment of well‐differentiated neuroendocrine tumors: A preclinical study

Abstract: Peptide receptor radionuclide therapy ( 177 Lu-DOTATATE) causes DNA strand breaks and has been validated for well-differentiated neuroendocrine tumor treatment.Poly-(ADP-ribose)-polymerase inhibitors have also been used for malignant tumors with deficient DNA repair. We aimed to determine whether the poly-(ADP-ribose)polymerase inhibitor fluzoparib could enhance the anti-tumor effects of 177 Lu-DOTATATE in neuroendocrine tumor cells and xenografts. The neuroendocrine characteristics of NCI-H727 bronchial carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Olaparib radiosensitized cells to both 177 Lu-DOTATATE and EBRT, although not in all cell lines, and the synergistic effect was more pronounced in combination with EBRT (lower CDI and larger AF) compared to 177 Lu-DOTATATE. This radiosensitizing effect was previously shown by other groups with EBRT [ 25 , 26 ] and in SSTR-expressing xenograft mouse models using talazoparib [ 27 ] or fluzoparib [ 28 ] in combination with 177 Lu-DOTATATE. Nonetheless, the greater amount of DNA lesions generated by the higher dose rate of EBRT compared to 177 Lu-DOTATATE may lead to a higher number of cytotoxic DSBs following PARP inhibition (PARPi), and therefore may explain the higher radiosensitizing potential.…”
Section: Discussionsupporting
confidence: 67%
“…Olaparib radiosensitized cells to both 177 Lu-DOTATATE and EBRT, although not in all cell lines, and the synergistic effect was more pronounced in combination with EBRT (lower CDI and larger AF) compared to 177 Lu-DOTATATE. This radiosensitizing effect was previously shown by other groups with EBRT [ 25 , 26 ] and in SSTR-expressing xenograft mouse models using talazoparib [ 27 ] or fluzoparib [ 28 ] in combination with 177 Lu-DOTATATE. Nonetheless, the greater amount of DNA lesions generated by the higher dose rate of EBRT compared to 177 Lu-DOTATATE may lead to a higher number of cytotoxic DSBs following PARP inhibition (PARPi), and therefore may explain the higher radiosensitizing potential.…”
Section: Discussionsupporting
confidence: 67%
“…However, no information is available on the development of fibrosis and diarrhea and increased production of 5-HT in animals after the implantation of NCI-H727 cells. Therefore, its use as a model for CS has been not confirmed yet [ 69 , 70 , 71 ].…”
Section: Preclinical Models Of Carcinoid Syndromementioning
confidence: 99%
“…Additionally, Fu et al showed that the PARPi, fluzoparib, could potentiate the antitumor effect of 177 Lu-DOTATATE in NCI-H727 cells synergistically. This effect was achieved by arresting the cell cycle in the G1 phase and reducing the tumor volume [187]. Furthermore, the combination therapy of 177 Lu-DOTATATE with PARPi, Olaparib, reduced survival in different cell lines compared to RPT monotherapy [137].…”
Section: Combination Of Radiopharmaceuticals and Dna Damage Repair In...mentioning
confidence: 99%